Large-scale experimental warming reduces soil faunal biodiversity through peatland drying - Barreto, Carlos; Conceição, Pedro Henrique Silva; de Lima, Estevam Cipriano Araujo; Stievano, Luís Carlos; Zeppelini, Douglas; Kolka, Randall K.; Hanson, Paul J.; Lindo, Zoë (Frontiers in Environmental Science, 2023)
Boreal peatlands are important ecosystems for carbon cycling because they store 1/3 of the world’s terrestrial carbon in only ~3% of the global landmass. This high carbon storage capacity makes them a key potential mitigation strategy for increased carbon emissions induced by global climate warming. In high-carbon storage systems like peatlands, soil faunal communities are responsible for secondary decomposition of organic matter and nutrient cycling, which suggests they play an important role in the carbon cycle. Experiments have shown that warming can affect plant and microbial communities in ways that potentially shift peatlands from carbon sinks to sources. Although previous studies have found variable effects of climate change manipulations on soil communities, warming is expected to affect soil community composition mainly through reductions in moisture content, whereas elevated CO2 atmospheric concentrations are expected to only indirectly and weakly do so. In this study, we used a large-scale peatland field-based experiment to test how soil microarthropod (oribatid and mesostigmatid mite, and collembolan species abundance, richness and community composition) respond to a range of experimental warming temperatures (between 0 and +9°C) crossed with elevated CO2 conditions over four years in the Spruce and Peatland Responses Under Changing Environments (SPRUCE) experiment. Here we found that warming significantly decreased surface peat moisture, which in turn decreased species microarthropod richness and abundance. Specifically, oribatid and mesostigmatid mite, collembolan, and overall microarthropod richness significantly decreased under lower moisture levels. Also, the abundance of microarthropods increased under higher moisture levels. Neither warming nor elevated [CO2] affected microarthropods when analysed together or separately, except for the richness of mesostigmatids that significantly increased under warming. At the community level, communities varied significantly over time (except collembolans), and moisture was an important driver explaining community species composition. While we expect that the cumulative and interactive effects of the SPRUCE experimental treatments on soil faunal biodiversity will continue to emerge, our results already suggest effects are becoming more observable over time. Taken together, the changes belowground indicate potential changes in carbon and nitrogen cycles, as microarthropods are important players in soil food webs.